Morris Birkbeck treatise and scrapbook - Birkbeck, Morris, 1764-1825.
Manuscript treatise on the human emotions and a scrapbook believed to have been owned by Birkbeck. Scrapbook contains 17th to 19th century British newspaper clippings. Includes human interest stories, poetry, and public notices.
Pioneer, farmer, author, and state official of Illinois.
Collection material in English.
Keywords: Emotions; Poetry; Great Britain -- Social life and customs; Authors; Farmers; Pioneers; Public officials